Pengaruh Pemberian Kompres Hangat Terhadap Penurunan Intensitas Nyeri Menstruasi (Dismenorhea) Pada Remajaputri Kelas 7 Di SMP Muhammadiyah 14 Surabaya - Widoyanti, Virki; Prayoga, Dimas Hadi; kaonang, Mahardika putri; Antoh, Novalia (Jurnal Medicare, 2025)
Menstrual pain (dysmenorrhea) is a common problem experienced by adolescent girls and can disrupt learning activities at school. One non-pharmacological method that can be used to reduce pain is warm compresses. This study aims to determine the effect of warm compresses on reducing the intensity of menstrual pain in 7th-grade female students at Muhammadiyah 14 Junior High School, Surabaya. The research method used a pre-experimental design with a one-group pre-post test approach. The sample consisted of 13 adolescent girls selected through quota sampling techniques according to the inclusion criteria. The instrument used was a questionnaire, while data analysis was carried out using the Wilcoxon Signed Rank Test. The results showed that before the intervention, most respondents experienced mild pain, as many as 7 people (53.8%). After the application of warm compresses, the majority of respondents did not feel any pain at all (scale 0), namely 9 people (69.2%). The results of the Wilcoxon Signed Rank Test obtained a p value = 0.001 (p <0.05), which means there is a significant effect of warm compresses on reducing the intensity of menstrual pain. The conclusion of this study is that warm compresses are effective in reducing menstrual pain in adolescent girls. It is hoped that this intervention can be used as a non-pharmacological alternative in treating dysmenorrhea.